Integrative Islamic Education for Disability Inclusion: A Psycho-Juristic Literacy Model in Indonesian Pesantren - Fathul Fauzi; Muhamad Ripin Ikwandi; Ahmad Hariyadi; M. Aziz Mukti (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Disability inclusion has become an important concern in Islamic education; however, inclusive practices in pesantren are often limited to institutional accommodation and have not fully transformed students’ value orientations toward disability. This study examines the implementation of psycho-juristic literacy as an integrative Islamic education model for strengthening disability inclusion in Indonesian pesantren. The novelty of this study lies in the integration of social psychology, Islamic jurisprudence, and critical literacy within a psycho-juristic literacy framework to promote justice-based and dignity-oriented perspectives on disability. Using a qualitative Participatory Action Research (PAR) design, the study was conducted from January to June 2025 at Pesantren Inklusi Sabilillah, Probolinggo, East Java, Indonesia. Data were collected through participatory observation, semi-structured interviews, focus group discussions, and documentation involving 28 participants, including santri, educators, and pesantren administrators. Data were analyzed through data condensation and thematic analysis integrated within iterative cycles of planning, action, observation, reflection, and evaluation. The findings reveal that psycho-juristic literacy facilitated a significant transformation in participants’ understanding of disability, shifting from charity-based perceptions toward justice-based, dignity-oriented, and rights-centered perspectives grounded in Islamic values. This transformation was reflected in changes in attitudes, social interactions, peer collaboration, and inclusive educational practices. The study also found that integrating psychological awareness, Islamic juridical reasoning, and critical reflection strengthened the internalization of inclusive values and fostered a more inclusive pesantren culture. This study contributes to the development of integrative Islamic education by offering an empirically grounded model that bridges theological principles, social psychology, and critical pedagogy for disability inclusion. The findings suggest that psycho-juristic literacy has the potential to support sustainable inclusive education and promote socially transformative learning within Islamic educational institutions.